The Control of the Indian Bookworm Beetle, Gastrallus indicus Reitter (Coleoptera: Anobiidae), by the Heat Treatment, together with Observations on the Posttreatment Viability of the Larvae - Roonwal, M. L.; Chatterjee, P. N. (Indian Forester, 1951)
No abstract